T-cell receptor gamma--delta lymphocytes and Eimeria vermiformis infection. - Rose, M E (1996)
The role of T-cell receptor gamma--delta T lymphocytes in coccidiosis was examined by determining the course of infection with Eimeria vermiformis in BALB/c mice depleted of gamma--delta lymphocytes by treatment with GL3 monoclonal antibody. The replication of the parasite in primary infections was not greatly, or consistently, affected by this treatment, and there was no correlation between the extent of depletion of small intestinal intraepithelial lymphocytes and the number of oocysts produced. The resistance of immunized mice to challenge was not compromised by depletion of intraintestinal epithelial lymphocytes when their depletion was effected at the time of primary infection and/or administration of the challenge inoculum. Thus, T-cell receptor gamma--delta T lymphocytes do not appear to be crucial to the establishment, or the control, of primary infection with E. vermiformis and are not principal mediators of the solid immunity to challenge that this infection induces.